2012
DOI: 10.1016/j.jog.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The thermal state and strength of the lithosphere in the Spanish Central System and Tajo Basin from crustal heat production and thermal isostasy

Abstract: Keywords:Heat flow Thermal structure Strength envelopes, Rheology Continentallithosphere Iberian PeninsulaIn this work we have modeled the thermal structure of the lithosphere of the Spanish Central System and the Tajo Basin, and their implications for lithospheric strength. For this, we have used refined heat producing elements (HPE) values to obtain new estimates of heat production rates in the Spanish Central System and Tajo Basin areas, which have been used joined to the relation between topography and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…The surface heat flow ranges from 60 to 85 mW m -2 , with the highest values in the Central System (Fernàndez et al, 1998;Jiménez-Díaz et al, 2012). The heat production in the upper crust ranges from 0.2-4.7 µW m -3 in the granitic rocks and from 0.8-2.3 µW m -3 in the metamorphic rocks (Fernàn-dez et al 1998;Jiménez-Díaz et al, 2012), whereas it barely exceeds 1 µW m -3 in the lower crust (Villaseca et al, 1999(Villaseca et al, , 2005Jiménez-Díaz et al, 2012).…”
Section: Structure Composition and Heat Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface heat flow ranges from 60 to 85 mW m -2 , with the highest values in the Central System (Fernàndez et al, 1998;Jiménez-Díaz et al, 2012). The heat production in the upper crust ranges from 0.2-4.7 µW m -3 in the granitic rocks and from 0.8-2.3 µW m -3 in the metamorphic rocks (Fernàn-dez et al 1998;Jiménez-Díaz et al, 2012), whereas it barely exceeds 1 µW m -3 in the lower crust (Villaseca et al, 1999(Villaseca et al, , 2005Jiménez-Díaz et al, 2012).…”
Section: Structure Composition and Heat Flowmentioning
confidence: 99%
“…Several studies have addressed the estimate of lithospheric strength to explain these characteristics (Van Wees et al, 1996;Gómez-Ortiz 2001;Tejero and Ruiz 2002;Gómez-Ortiz et al, 2005b;Pérez-Gussinyé and Watts 2005;Jiménez-Díaz et al, 2012). Although strength strongly depends on the structure, temperature, composition, strain rate and stress regime of the lithosphere (Fernàndez and Ranalli 1997;Afonso and Ranalli 2004;Ruiz et al, 2006;Fernández-Ibáñez and Soto 2008;Burov 2011;Jiménez-Díaz et al, 2012), average crustal and mantle structures over large areas, diverse lithologies (hard/ soft) and stress regimes (compression/tension) were assumed in those previous studies. Consequently, these strength estimates are varied, and even shallow crustal ductile levels or brittle-ductile transitions are obtained that do not totally explain the intraplate seismicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiménez-Díaz et al (2012) suggested a value ranging between 81-83 mWm -2 of the surface heat flow for the Tagus Basin, involving mantle processed to the continuous uplift of the SCS. Models developed by these authors indicate a maximum thickness for the upper crust of 16 km within the Tagus Basin and of 11 km for the SCS.…”
Section: Geodynamic and Geologic Backgroundmentioning
confidence: 99%
“…However, fault parametrization for hazard purposes is still a controversy. In this sense, the geothermal features (Jiménez-Díaz et al, 2012), the analogue models of the lithosphere (Fernández-Lozano et al, 2011) and numerical models (Martín-Velázquez et al, 2009) underneath the SCS, could shed light on the fault width which could be load for trigger either moderates or destructive earthquakes.…”
Section: Geodynamic and Geologic Backgroundmentioning
confidence: 99%